2011
DOI: 10.1007/s11814-010-0500-4
|View full text |Cite
|
Sign up to set email alerts
|

Microwave synthesis of mesoporous WO3 doping with bismuth and photocatalytic oxidation of water to H2

Abstract: Mesostructured tungstic acid was prepared from Na 2 WO 4 with protonated cation-exchange using a surfactant cetyltrimethyl ammonium bromine (CTAB) as the structure-directing agent under microwave radiation. The surfactant was removed by high-temperature calcination, microwave radiation extraction and Soxhlet extraction, respectively. The effects of these methods for removal of the surfactant were investigated in detail. XRD, TEM, FT-IR and UV-Vis were employed to characterize the mesostructured materials. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…3, the IR bands appeared at the wavenumber of 764 cm −1 , 754 cm −1 and 609 cm −1 for WO 3 , are the characteristics intensity peaks of Keggin structure of as-synthesized WO 3 . 50 These characteristic peaks of tungsten oxide are associated to the terminal vibration (764 cm −1 ), corner-sharing vibration (754 cm −1 ) and superoxide vibration (609 cm −1 ). In addition, W-O-W stretching vibration could be easily noticed at wavenumber of 600 cm −1 and 1,000 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…3, the IR bands appeared at the wavenumber of 764 cm −1 , 754 cm −1 and 609 cm −1 for WO 3 , are the characteristics intensity peaks of Keggin structure of as-synthesized WO 3 . 50 These characteristic peaks of tungsten oxide are associated to the terminal vibration (764 cm −1 ), corner-sharing vibration (754 cm −1 ) and superoxide vibration (609 cm −1 ). In addition, W-O-W stretching vibration could be easily noticed at wavenumber of 600 cm −1 and 1,000 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…A great variety of synthesis route (see Chap. 3) are used for the synthesis of doped semiconductors which included mainly coprecipitation (Liu et al 2005), sol-gel (Jaimy et al 2011), hydrothermal (Jiang et al 2014), solvothermal , Pechini method (Wang and Cao 2011), combustion (Ahmad et al 2013), microwave (Li et al 2014a), ultrasound (Omidi et al 2013, and in the form of thin films by sol-gel (Wang and Cao 2011) deposited by dip coating (Zou et al 2011).…”
Section: Ion-doped Semiconductors (M + ¼ Transition Metal Ion)mentioning
confidence: 99%
“…For this purpose, Zou et al (2011) reported the microwave synthesis of mesoporous Bi-doped WO 3 materials in presence of cetyltrimethyl ammonium bromine (CTAB) as structure-directing agent. The amount of Bi 2 O 3 loading was optimized in a 7.0 wt % for the production of H 2 .…”
Section: Ion-doped Semiconductors (M + ¼ Transition Metal Ion)mentioning
confidence: 99%